Characterization and antimicrobial activity of Amycolatopsis strains isolated from Thai soils - Piyapat Sripairoj, Khanit Suwanborirux and Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2013)
The isolation and screening of antimicrobial activity of 3 actinomycete strains isolated from soil samples collected in Chaiyaphum, Nan and Phatthalung provinces, Thailand were carried out. Strains S39-7, KC19-1 and K57-1 were belonged to the genus Amycolatopsis based on their phenotypic and chemotaxonomic characteristics. On the basis of 16S rRNA gene sequence analysis, strain S39-7 was closely related to Amycolatopsis albidoflavus KCTC 9471T (99.2%). Strains KC19-1 and K57-1 were closely related to A. kentuckyensis NRRL B-24129T with 99.3 and 99.2% similarity, respectively. All of them contained meso-diaminopimelic acid (DAP) in cell wall peptidoglycan and had MK-9 (H4) as a major menaquinones. The DNA G+C contents of the strains ranged from 67.2 to 73.4 mol%. On secondary screening of antimicrobial activity, the ethyl acetate extract of the fermentation products of strain S39-7 was active against Staphylococcus aureus ATCC 6538, Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25922, Kocuria rhizophila ATCC 9341, and Pseudomonas aeruginosa ATCC 27853 while strain KC 19-1 was active against only S. aureus ATCC 6538. Strain K 57-1 was active against E. coli ATCC 25922 and K. rhizophila ATCC 9341. In addition strain S39-7 could inhibit against methicillin resistant (MRSA) S. aureus 266.
Keywords: Actinomycetes, Amycolatopsis, antimicrobial activity, soil.